Association of Infestation of Gastrointestinal Nematode With Altitudes of Location of Cattle Raising in Two Different Districts in Aceh Province - Zulfikar Zulfikar; Sayed Umar; Teuku Reza Ferasyi; Maruf Tafsin (The International Journal of Tropical Veterinary and Biomedical Research, 2018)
This study was aimed to measure the prevalence and the association of altitude of location of raising to the risk of infestation of gastrointestinal nematode in cattle. The study was conducted using cross sectional approach. A purposive sampling method was used to select the location of study (subdistricts and villages) in the two Districts. The inclusion criteria for the lowland were the location with altitude 200 m above sea level and the subdistricts (villages) of North Aceh District. The exclusion criteria for lowland was the location 200 m above sea level. Then, the inclusion criteria for the highland were the location with altitude 200 m above sea level and the subdistricts (villages) of Central Aceh District. The exclusion criteria for lowland was the location 200 m above sea level. A random sampling was used for selection of cattle for collecting faecal sample in two locations of study. A total number of 201 cattle, both male and female, were obtained for taking faecal sample from the two Districts. Faecal sample was examined for the existence of eggs of gastrointestinal nematode. The examination was conducted using floating method. Data were analyzed descriptively. The measurement of association of altitude of location of cattle raising and sex of animals to the risk of infestation of gastrointestinal nematode were analyzed using odds ratio (OR) estimation and continued with chi-square test. The results showed a higher prevalence of gastrointestinal nematode infestation in cattle of Lowland location (25%) as compared to Highland (5.8%). As for the altitude, the cattle raising in Lowland were more than 5 times higher risk for infestation of gastrointestinal nematode as compared to Higher land location (P0.005). The female cattle in Lowland was higher risk (6.18) for infestation than Highland (P0.01). A similar trend was obtained for male cattle which higher risk in Lowland (4.12) as compared to Highland, but it was not significant (P0.05). In conclusion, by considering the altitude of location, the cattle raising in Lowland were more than 5 times higher risk for infestation of gastrointestinal nematode as compared to Higher land location. There is a variation of risk between female and male cattle in different altitude.